Mechanical behaviour of unsaturated soil as Crushed Rock Base (CRB) layer under dynamic loads - Siripun, Komsun; Jitsangiam, Peerapong; Nikraz, Hamid (The Hong Kong Geotechnical Society and The Hong Kong Polytechnic University, 2011)
This paper reports the mechanical behaviour of crushed rock with unsaturated condition under repeated cyclic loading triaxial (RLT) tests performed at different stress levels, in order to investigate the effect of moisture content to crushed rock performances. Road surface rutting is the core basis of damage in flexible pavements which the mainly significant is crushed rock still unclearly thoughtful regarding mechanical behaviour under real situation. RLT tests used to describe the various mechanical responses of unbound granular materials (UGMs) by macro-mechanical observations. The main study focused on the influence of the moisture content moreover crushed rock will be determined the moisture content limit and the effects should be considered in this behaviour for crushed rock base.